Peningkatan Partisipasi dan Hasil Belajar Siswa Kelas V Menggunakan Media Pop Up Book pada Mata Pelajaran Bahasa Indonesia di SDN 47 Mataram - Ulfa, Bellia; Saputra, Heri Hadi; Irmayani, Ari (Mataram University, 2025)
This study aims to improve students’ participation and learning outcomes in the Indonesian language subject for fifth-grade students at SDN 47 Mataram through the use of Pop Up Book media. This research employed a Classroom Action Research (CAR) method conducted in two cycles, with each cycle consisting of the stages of planning, implementation, observation, and reflection. The results showed that the use of Pop Up Book media significantly enhanced students’ participation and learning outcomes. The average student score increased from 76 in the pre-cycle to 79 in the first cycle and reached 89 in the second cycle. The percentage of students achieving mastery learning also rose from 35.13% in the pre-cycle to 54.05% in the first cycle and reached 89.18% in the second cycle. Therefore, the use of Pop Up Book media proved to be effective in improving both students’ participation and learning outcomes and can serve as an alternative instructional medium to enhance the quality of classroom learning.